Agriculture beyond the oil palm development in Jambi province Participatory Prospective Analysis - Mienmany, S. (Center for International Forestry Research, 2013)
In the recent years, oil palm sector has become a key part of the Indonesian economy. The growth of oil palm has open a debate between conservation and development: some see palm oil as an alternative resource for the mitigation of climate change and for the improvement of people's livelihood. The others see oil palm cultivation as harmful to biodiversity which creates social conflicts. In this research, based on the lessons learnt from Senamat Ulu and Batu Kerbau villages, Bungo district, we discuss the prospective views of the local people who are dealing with oil palm development in Jambi Province, Indonesia. Socio-economic analysis and stakeholder analysis were conducted to support the Participatory Prospective Analysis. The land use profitabilities of rubber monospecific and oil palm plantations are higher than for rubber agroforest and even more than for rice and swidden cultivations. The extension of contracts between local land owners and oil palm companies carries the risk of land grabbing and indirectly impacts the community forests, in spite of their village protected status. Primary Cooperative Credit for Members' scheme contracts (KKPA) are often unclear and long negotiations can take place between oil palm companies, local investors and villagers. Participatory Prospective Analysis workshops withlocal stakeholders contributed to clarify the benefits and costs of the various scenarios for possible future of the villages. Improved seedlings, road accessibility and improved capacity building are needed, both on the short term and long term, strengthening the future of the people in the next 30 years.